(untitled) (International Current Pharmaceutical Journal, 2016)
In the late 1970s, rapid disintegrating drug delivery system was developed as an alternative to capsules, tablets and syrups for geriatric and pediatric patients having problems in swallowing. To overcome the need, number of orally disintegrating tablets which disintegrate within one minute in mouth without chewing or drinking water were commercialized. Then later, oral drug delivery technology had been improved from conventional dosage form to modified release dosage form and developed recently rapid disintegrating films rather than oral disintegrating tablets. Oral disintegrating film or strips containing water dissolving polymer retain the dosage form to be quickly hydrated by saliva, adhere to mucosa, and disintegrate within a few seconds, dissolve and releases medication for oro-mucosal absorption when placed in mouth. Oral film technology is the alternative route with first pass metabolism. This review give a comprehensive detail of materials used in ODF, manufacturing process, evaluation tests and marketed products. Mahboob et al., International Current Pharmaceutical Journal, November 2016, 5(12): 111-117 http://www.icpjonline.com/documents/Vol5Issue12/03.pdf